Healthy Lifestyle and Behavior: A Preventive Strategy to Address the Global Burden of Disease - Ningsih, Kori Puspita; Ningsih, Dewi Andariya; Ambarwati, Eny Retna Ambarwati (PT. Anagata Sembagi Education, 2025)
The increasing burden of global diseases, particularly non-communicable diseases (NCDs) such as diabetes, hypertension, and cardiovascular disorders, has become a major challenge for healthcare systems in many countries, including Indonesia. This study aims to analyze the relationship between lifestyle and healthy behavior with the effectiveness of preventive strategies in reducing disease risk. The research used a quantitative approach through a survey of 190 productive-age respondents in urban and semi-urban areas. Data were collected using closed-ended questionnaires based on a Likert scale and analyzed using Pearson correlation and simple linear regression. The results showed a positive and significant relationship between a healthy lifestyle particularly physical activity and stress management and the preventive strategies adopted by the community. The main barriers in adopting a healthy lifestyle include limited time, access to facilities, and low health literacy. These findings emphasize the importance of an integrated promotive-preventive approach through cross-sectoral policies and support from digital technology to strengthen healthy living behavior as the foundation of sustainable public health.